Glow inside & out - Auni Baharin (Puteh Press, 2022)
Happiness and well-being are adornments of this temporary life. They lift up the heaviness in our chests when navigating through obstacles and challenges in our journey towards the eternal destination; akhirah. Though happiness in its truest sense is a gift from the Creator, we also hold some degree of power on the reigns of our life to improve our well-being. Inspired by the scientific input from Positive Psychology and understandings from the al-Quran and Sunnah, Glow Inside & Out presents to you 10 steps to rejuvenate your happiness and well-being. If following the 10-step Korean skincare routine can give you radiant "glass skin", then the author is hopeful that the 10 main insights from this book could ignite the spark to your inner glow.